2019
DOI: 10.1089/ten.tea.2017.0440
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of -5p and -3p Strands of miR-145 and miR-140 During Mesenchymal Stem Cell Chondrogenic Differentiation

Abstract: The chondrogenic differentiation of mesenchymal stem cells (MSCs) is mediated by transcription factors and small noncoding RNAs such as microRNAs (miRNAs). Each miRNA is initially transcribed as a long transcript, which matures to produce -5p and -3p strands. It is widely believed that the mature and functional miRNA from any given pre-miRNA, usually the -5p strand, is functional, while the opposing -3p strand is degraded. However, recent cartilage literature started to show functional -3p strands for a few mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 37 publications
0
9
1
Order By: Relevance
“…We predicted 164 miRNAs targeting KLF4 using the ENCORI database ( http://starbase.sysu.edu.cn/ ). Among them, 8 KLF4-binding miRNAs were verified in previous studies: hsa-miR-346 [ 21 ], hsa-miR-140-3p [ 22 ], hsa-miR-18a [ 23 ], hsa-miR-15a [ 24 ], hsa-miR-103a [ 25 ], hsa-miR-7 [ 26 ], hsa-miR-135 [ 27 ], and hsa-miR-29a [ 28 ]. Furthermore, targeted miRNAs of downregulated lncRNAs were predicted using the InCeDb database ( http://gyanxet-beta.com/lncedb/ ).…”
Section: Methodsmentioning
confidence: 85%
“…We predicted 164 miRNAs targeting KLF4 using the ENCORI database ( http://starbase.sysu.edu.cn/ ). Among them, 8 KLF4-binding miRNAs were verified in previous studies: hsa-miR-346 [ 21 ], hsa-miR-140-3p [ 22 ], hsa-miR-18a [ 23 ], hsa-miR-15a [ 24 ], hsa-miR-103a [ 25 ], hsa-miR-7 [ 26 ], hsa-miR-135 [ 27 ], and hsa-miR-29a [ 28 ]. Furthermore, targeted miRNAs of downregulated lncRNAs were predicted using the InCeDb database ( http://gyanxet-beta.com/lncedb/ ).…”
Section: Methodsmentioning
confidence: 85%
“…Accumulated evidences have shown that post-transcriptional regulation by microRNAs (miRNAs) was involved in the osteogenic and chondrogenic differentiation of MSCs [27,41] . It was a practical approach to mediate the chondrogenic differentiation of MSCs by manipulating the expression of speci c miRNAs [42][43][44] . A variety of miRNAs participated in the processes of irisin on osteogenic differentiation of MSCs, browning of white adipocytes, and anti-in ammation [19,[45][46] .…”
Section: Discussionmentioning
confidence: 99%
“…KSRP processes and controls the expression of miRNAs (miR-145, miR-150, let-7a) [29,42,43] other than miR-155, and the proposed mechanism involves recruitment of proteins such as Drosha, DGCR8, and Dicer [29]. Interestingly, all the miRNAs controlled by KSRP have the 5p strand as the dominantly expressed strand (guide strand) and the 3p strand as the passenger strand [44][45][46]. Thus, KSRP may be participating in strand selection by bringing specific proteins into the Dicer complex that enhances the thermodynamic stability [47] of the 5p strand binding to the Dicer protein.…”
Section: Discussionmentioning
confidence: 99%